Mediated Violence - Bender, Stuart (De Gruyter Mouton, 2018)
This chapter outlines some of the key positions adopted by scholarly approaches to mediated violence and shows how contingent factors in the new media environment collapse the producer-consumer relationship in terms of screen recordings of real life violence, which has important implications for the effect and affect of such material. The chapter contrasts psychology based media-effects research with the emphasis on textual analysis taken by communication studies. While some findings of the media-effects research appears to suggest that mediated forms of violence contribute to such behavior in the real world, communications scholars take a nuanced approach and show that there are a substantial range of aesthetic and reception issues involved. This chapter considers traditional cinema violence, “leaked” violent videos on websites, and also the emergence of so-called “performance crime” such as murder videos posted to Facebook and other social media platforms. Given the significant ways in which science and cultural-communications studies have been able to complement each other in this area – as much as they have claimed to be in friction – it is perhaps possible for new modes of multidisciplinary research to explore both the impact of new mediated violence.